Roles of N6-methyladenosine (m6A) modifications in gynecologic cancers: mechanisms and therapeutic targeting - Jiahua Chen; Bao Guo; Xiaojing Liu; Jing Zhang; Junhui Zhang; Yuan Fang; Suding Zhu; Bing Wei; Yunxia Cao; Lei Zhan (Experimental Hematology & Oncology, 2022)
Abstract Uterine and ovarian cancers are the most common gynecologic cancers. N6−methyladenosine (m6A), an important internal RNA modification in higher eukaryotes, has recently become a hot topic in epigenetic studies. Numerous studies have revealed that the m6A-related regulatory factors regulate the occurrence and metastasis of tumors and drug resistance through various mechanisms. The m6A-related regulatory factors can also be used as therapeutic targets and biomarkers for the early diagnosis of cancers, including gynecologic cancers. This review discusses the role of m6A in gynecologic cancers and summarizes the recent advancements in m6A modification in gynecologic cancers to improve the understanding of the occurrence, diagnosis, treatment, and prognosis of gynecologic cancers.